1999
DOI: 10.1177/107110079902001204
|View full text |Cite
|
Sign up to set email alerts
|

Role of Metatarsus Primus Elevatus in the Pathogenesis of Hallux Rigidus

Abstract: Metatarsus primus elevatus has been suggested as a primary causative factor in the pathogenesis of hallux rigidus. The purpose of this investigation was to define the role of elevation of the first ray in the pathogenesis of hallux rigidus by comparing patients with known hallux rigidus with a control population. We reviewed 264 lateral weightbearing radiographs from 81 patients with hallux rigidus, 50 asymptomatic volunteers, and 64 patients diagnosed with isolated Morton's neuroma. Results revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
84
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 9 publications
(2 reference statements)
2
84
1
Order By: Relevance
“…The variability in individual subject responses to orthotic use is not unique to our investigation 2,5,15,22,34,36,42,49 and there are excellent review papers that have summarized the wide-ranging effects of orthotic intervention. 1,24,41 To further investigate individual subject responses, we used the smallest real difference (SRD) to indicate the magnitude of change for an individual across conditions that is beyond the expected trial-to-trial variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The variability in individual subject responses to orthotic use is not unique to our investigation 2,5,15,22,34,36,42,49 and there are excellent review papers that have summarized the wide-ranging effects of orthotic intervention. 1,24,41 To further investigate individual subject responses, we used the smallest real difference (SRD) to indicate the magnitude of change for an individual across conditions that is beyond the expected trial-to-trial variability.…”
Section: Discussionmentioning
confidence: 99%
“…This angle reflects the anterior component of the arch height measurement, such that an increase in the metatarsal declination angle corresponds to an elevation of the anterior portion of the medial longitudinal arch. 6,22,26 An increase in the metatarsal declination angle also places the first metatarsal in a position of relative plantar flexion, which is considered favorable for the propulsive phase of gait. 43,44,47 We selected the metatarsal declination angle to assess whether a change, if it did occur with orthotic use during relaxed standing, would parallel the direction of change in first MTP joint dorsiflexion during gait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of the included studies failed to clearly describe the distributions of principal confounders in each of the participant groups. The study by Zgonis et al 48 was the only one to adequately identify the population from which the study participants were derived; no studies adequately determined whether study participants were Description of Studies Included in the Review Horton et al (1999) Clinical and radiographic evidence of hallux limitus. Joint degeneration radiographically graded 1 to 3 in accordance to Hattrup representative of the source population from which they were recruited; no studies adjusted for confounding variables in their statistical analysis; and no studies specifically reported matching case and control participants for age and sex ( ).…”
mentioning
confidence: 99%